Cross-Frame Potential. (1st November 2022) - Aceska, Roza; Kaczanowski, McKenna
Abstract: We study a cross-frame potential function, which appraises the cross correlation between a frame and its dual. We analyze this new function to determine what information the cross-frame potential value can reveal about the relationship between the two frames. We also define a cross frame potential function for fusion frames, and study its properties for special types of fusion frames.